Primary Teachers’ and Students’ Images of Teachers and Learning Environments - Şahin Kalyon, Demet (International Electronic Journal of Elementary Education, 2020)
The purpose of the current study is to elicit both primary teachers’ and their students’ images of the primary teacher in science classes and to discuss the similarities and differences between the teachers’ image of the primary teacher in science classes and the students’ image of the primary teacher in science classes. In the current study, the data were collected by using The Draw-A-Science –Teacher-Test Checklist (DASTT-C) developed by Thomas et al. (2001). The DASST-C is a useful tool to show how the science teaching environment is and how teacher behaviors in the science teaching environment are. A total of 50 primary teachers and 120 primary school students (3rd and 4th grades) participated in the current study. The obtained data were analyzed by using the DASST-C Score sheet and the criteria proposed by Şahin Kalyon (2020) to evaluate the learning environment. It was concluded that the participating teachers have almost equally adopted each teaching style. In other words, the teachers have equally adopted student-centered, teacher-centered, and both teacher and student-centered teaching. In the drawings of the participating primary school students, the most frequently depicted image of the teacher was found to be the teacher having an explicit teaching style, followed by the exploratory teaching style and conceptual teaching style. In other words, most of the students depicted a teacher who has adopted the teacher-centered teaching in their drawings. As a result of the analyses, it was concluded that the students of the teachers having the exploratory and conceptual teaching styles largely drew teachers in their pictures having the exploratory teaching style. The students of the teachers having the explicit teaching style also largely depicted teachers in their drawings having the explicit teaching style. Considering these findings, it can be argued that the teaching style of the teacher affects his/her students’ image of the teacher.